Implementation of SMART Adult Learning Strategy on Educational Culture Exchange Workshop: Integrating International Language in Learning Experiences to Prepare Young Generation for Global Challenges - Lenni Mantili Hutauruk; Rosane Medriati; Kashardi Kashardi; Lia Haryana; Dwi Ismawati (CV Media Inti Teknologi, 2024)
This article aims to describe how community service through implementation of the SMART Adult Learning Strategy to prepare the young generation (in English ability) for global challenges. The activity was carried out in October 2023 at Bengkulu University, with a total of 51 participants in the workshop who were students, teachers, community members, and lecturers from various institutions. To see the workshop's impact on participant English Self-Efficacy which is closely related to their readiness to communicate with international, English-speaking countries, instrument of a closed questionnaire with 7 answer choices of English Self-Efficacy (ESE) Scale was used. The data then analysed by descriptive statistical analysis. The results showed that there was a significant increase in ESE level between pre-implementation and after the implementation. Selected ESE tested had significant increases (on average) were: discussing in English with classmates some topics in which they are interested with a 20% increase; participants' confidence in understanding songs in English was 17%, while the on reading news in English was 17%. The highest increase in ESE level was in understanding English articles about Indonesian culture which has an average increase of 21%. The respondents who believed to have more confidence in their ESE as there was a positive statements impact range between 16-21% increase in the tested ESE level. So, it can be concluded that The implementation of the SMART Adult Learning Strategy to prepare the young generation for the global challenges from the perspective of English ability received a positive response from the participants.